Hydrocolloid Membrane Dressing in Shearing Injuries in the Distal Part of the Pelvic Limbs in Dogs - Pacheco, Larissa Teixeira; Lopes Muzzi, Leonardo Augusto; Henrique, Bruna Frias; Freitas, Débora de Oliveira; Momesso, Eric Orlando; Monroe Rocha, Mariana; Silva Domingues, Fernanda Cristina; Lázaro Muzzi, Ruthnea Aparecida (Acta Scientiae Veterinariae, 2019)
Background: Shearing wounds on the limbs of dogs usually affect the regions distally from the radiocarpal joint at the thoracic limb and from the tibiotarsal joint at the pelvic limb. The tissue coverage and re-epithelialization of the injured region are important factors that should be considered in the definitive surgical treatment. The hydrocolloid membrane promotes selective autolytic debridement and accelerates the formation of granulation tissue and epithelialization. The present study aims to describe the treatment with hydrocolloid membrane dressing of three cases of shearing wounds with concomitant orthopedic injuries in the pelvic limbs of dogs. Case: Three dogs with pelvic limb injuries after vehicular trauma were selected for treatment. Two patients had shearing lesions on the medial aspect of the pelvic limb with exposure of the tibia and fibula, the talus and the tibiotarsal joint, associated with bone loss on the medial surface of the limb and rupture of the medial collateral ligament of the tarsus. Another patient had a shearing wound on the dorsal surface of the distal region of the pelvic limb, with injury of the digital extensor tendons and bone exposure of the second and third metatarsals. Initially, the surgical debridement of the lesion was performed and during the first five days after trauma the wound was cleansed with chlorhexidine solution and topical application of crystallized sugar daily. In this initial period a dry adherent dressing was used on the lesions, without bandages for immobilization of the pelvic limb. In all dogs, the hydrocolloid membrane was applied from the sixth day after initial wound management. Immediately after the application of the hydrocolloid membrane, temporary immobilization of the affected pelvic limb with a padded Robert Jones bandage was performed. The first changes of the hydrocolloid membranes were performed after five days of their use. Subsequently, the membranes changes became more spaced and were performed within a period between 7 to 10 days. After wound repair, in one of the dogs with a shearing injury in the medial surface of the pelvic limb, the rupture of the medial collateral ligament was surgically treated with the use of anchor screws and nylon thread for the ligament reconstruction. The other dog presented with lesion in the medial surface of the pelvic limb and collateral ligament rupture was not submitted to late orthopedic surgical treatment. The latter was clinically managed and developed valgus deviation of the affected pelvic limb, but with functional use of the limb. The dog with a shearing lesion on the dorsal surface of the pelvic limb and injury to the extensor tendons was managed conservatively with use of orthosis and, after 45 days of initial trauma, the dog showed a functional lameness and absence of pain in the affected limb. Discussion: In all animals, the hydrocolloid membrane was applied on the wound from the sixth day after the initial lesion treatment. As the wound was healing the hydrocolloid dressing was changed in a more spaced period and this management allowed the proper tissue healing without complications. The wound treatment with dressing was aided by the application of temporary limb immobilization with padded bandage, until a late orthopedic procedure was performed or a final clinical resolution occurred. In general, the shearing wounds healed in a period ranging from 28 to 38 days. In conclusion, the use of the hydrocolloid membrane dressing associated with limb immobilization was an effective method for treatment of patients with shearing wounds, allowing proper healing of the affected tissues and good recovery of the limb function. The hydrocolloid membrane has the main benefits to allow the spaced changes of the dressings and the ability to stimulate the rapid healing of the wound.